2018
DOI: 10.1111/jph.12773
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition, antifungal, antioxidant and antimutagenicity properties of bioactive compounds from fungal endophytes associated with Thai orchids

Abstract: Some plant‐derived bioactive compounds produced by fungal endophytes have been proven to have antimicrobial and antioxidant activities. In this study, endophytic fungi were isolated from 20 orchid samples collected in northern Thailand from 12 genera of orchids. In total, 97 isolates were isolated from the leaves (44.3%), stems (40.2%) and flowers (15.5%) of the orchid samples. The antifungal activity was investigated of the endophytic isolates against the plant pathogenic fungi. The results showed that 13 end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…For instance, using the DPPH radical scavenging assay, Hamzah et al (2018) reported the free radical scavenging potential of methanol-extract of F. lateritium endophyte of Rhizophora mucronata. Similarly, the phenolic content (160.51 mg of GAE/g of extract) and the free radical scavenging activity (IC 50 89.61 µg/mL) of ethyl acetate extract of F. oxysporum isolated from the flower part of Dendrobium lindleyi was also reported (Bungtongdee et al 2019). Likewise, the free radical scavenging activity (IC 50 482 μg/mL) of crude metabolites from endophytic F. tricinctum was reported by Vasundhara et al (2016).…”
Section: Antioxidant and Antiaging Activities Of Metabolites From Fusarium Speciesmentioning
confidence: 74%
See 1 more Smart Citation
“…For instance, using the DPPH radical scavenging assay, Hamzah et al (2018) reported the free radical scavenging potential of methanol-extract of F. lateritium endophyte of Rhizophora mucronata. Similarly, the phenolic content (160.51 mg of GAE/g of extract) and the free radical scavenging activity (IC 50 89.61 µg/mL) of ethyl acetate extract of F. oxysporum isolated from the flower part of Dendrobium lindleyi was also reported (Bungtongdee et al 2019). Likewise, the free radical scavenging activity (IC 50 482 μg/mL) of crude metabolites from endophytic F. tricinctum was reported by Vasundhara et al (2016).…”
Section: Antioxidant and Antiaging Activities Of Metabolites From Fusarium Speciesmentioning
confidence: 74%
“…According to Bungtongdee et al (2019), extract from F. oxysporum with strong antimutagenic activity was found to be composed of gibepyrone A, pyrrolo [1, 2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) and indoleacetic acid as major components. Another study by Tiwari et al (2014) reveals that as compared to 1,5-pentanediol, 2,3-pentanediol (105) isolated from F. oxysporum endophyte of Curcuma amada was found to improve antiaging properties against Caenorhabditis elegans.…”
Section: Antioxidant and Antiaging Activities Of Metabolites From Fusarium Speciesmentioning
confidence: 99%
“…Isolates of Rh -like fungi forming a mycorrhizal symbiosis with orchids are used due to their non-pathogenic action for biological protection of plants against their phylogenetically related representatives, which cause significant economic losses [ 18 , 19 ]. Orchid tissues contain a wide range of fungi that grow endophytically, which have protective effects against plant pathogens [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi obtain nutrients, protection, and growing sites from host plants. Several endophytic fungal species have been reported to produce antibacterial, antifungal, antiviral, anti-inflammatory, and antitumor bioactive compounds that can protect host plants (Hussain et al 2014;Bungtongdee et al 2018;Praptiwi et al 2018;Ding et al 2019).…”
Section: Introductionmentioning
confidence: 99%